Cultural Assimilation among the Characters in Margaret Dillowy’s Novel “How to be an American Housewife” - Amirul Hakim Kilwouw; Dahlia D. Moelier; Sudirman Maca (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
The aims of the research are to find out the assimilation portrayed through the characters in the novel and to describe the impact of assimilation occurred towards the characters. The research applied the library research to get as many data from the novel and some books containing theories which connect to the research. The primary data was taken from Margaret Dilloway’s Novel “How to be an American Housewife”. The data was analyzed by using sociological approach and the theory of assimilation by Milton Gordon. The result shows that in the novel How to be an American Housewife can be found three models of assimilation. There are the classic and new assimilation model, the racial or disadvantaged model, and the segmented assimilation model. Besides that, Assimilation process give the big impacts towards the main character in the novel, Shoko and her daughter who grow up in the culture of American. The impacts cover almost all of life aspects of the Shoko then make her has no choice. She wants or not, like or dislike she has to accept the American culture and reduce her culture. She has to face many difficulties in daily life.